Compétences émergentes dans la pratique des professeurs des écoles débutants. Une approche psychophénoménologique. - Magali Boutrais (Presses universitaires de la Méditerranée, 2018)
Our research aims at understanding how builds itself the "I" professional of novice primary school teachers, from their point of view, by using the psychophenomenological approach and the explicitation interview (Vermersch, 1994). This epistemological approach coupled with the technique of the explicitation interview takes into account the subjectivity of the actors to document the progress of the actions in a past situation. The qualitative data collected with six primary school teachers are consisted of explicitation interviews and semi-directive interviews. The analysis of this corpus, directed to the understanding of the activity of the teachers, highlights the grips of information and decision-making made in class, during interactions with the pupils. The skills implemented by the novice teachers in situation as well as the underlying values result from the analysis of these data. This article presents the emergent skills under construction at primary school teachers. The links between these emergent skills and the items of the competence 4 of the "Référentiel des compétences professionnelles des métiers du professorat et de l'éducation" (2013) allow to question the stakes in the training of future primary school teachers.